The Influence of Leadership and Work Stress on Employee Performance at The Bandung City Regional Revenue Agency - Fahmi Dwi Bahari; Muhamad Dezan Fiera; Herman Sofyandi (Quantitative Economics and Management Studies, 2023)
Bandung City Revenue management agency is an agency engaged in city revenue and taxation, this agency is used as the object of this research, This research seeks to improve employee performance to be even better, with the factors used are leadership and stress work is also a variable in this study. The research method used is a descriptive and verificative method. The population used was employees of the Bandung Regional Revenue Agency which amounted to 37 people, the research sample used was 32 people. The analysis method uses multiple regression and hypothesis testing. The results of the study were obtained as a member of the Regional Revenue Agency of the city of Bandung with a fairly effective leadership with the highest level influenced by the factor of responsibility and the provision of guidance while the lowest is good relations to subordinates and the provision of freedom of opinion. The Regional Revenue Agency of Bandung city has a fairly good level of work stress, with the highest level of work stress being with the role demand factor and organizational leadership, while the lowest is the factor of task demands and demands between individuals. Employee performance is significantly influenced by leadership and work stress. Work stress is more domonan whereas leadership is lower. The highest factor in work stress is the demands of the role and leadership of the organization where both factors have a fairly high influence on stres levels employee work, while in leadership there is a lack of relationship between superiors and subordinates this affects employee performance and also freedom of opinion makes decreased employee performance, this affects the suitability.